2015
DOI: 10.1016/j.jcrs.2014.12.056
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a hyaluronic acid and carboxymethylcellulose ophthalmic solution on ocular comfort and tear-film instability after cataract surgery

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 5 publications
7
46
1
3
Order By: Relevance
“…Our results are in accordance to former published studies that reported significant improvement of TBUT and foreign body sensation when 0.1% sodium hyaluronate and 0.5% carboxymethylcellulose ophthalmic solution was additionally prescribed for the postoperative regime [29]. In fact, the effective postoperative management of the ocular surface that the additional artificial tears medication provides, improves patient satisfaction significantly with the surgical outcome and fosters the bond between the physician and the patient [30, 31].…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in accordance to former published studies that reported significant improvement of TBUT and foreign body sensation when 0.1% sodium hyaluronate and 0.5% carboxymethylcellulose ophthalmic solution was additionally prescribed for the postoperative regime [29]. In fact, the effective postoperative management of the ocular surface that the additional artificial tears medication provides, improves patient satisfaction significantly with the surgical outcome and fosters the bond between the physician and the patient [30, 31].…”
Section: Discussionsupporting
confidence: 91%
“…HA has a higher ocular retention compared to CMC or HPMC, and has also been shown to have effects on corneal epithelial cell healing in animal models45 and to improve corneal recovery in patients with superficial punctate keratitis compared to CMC 52. Larger studies have shown comparable results between CMC and HA with respect to the stabilization of the tear film after cataract surgery,53 and clinical trials using HA eye drops demonstrate the efficacy of this therapy for improving symptoms and clinical signs in moderate‐to‐severe dry eye disease over 3 months 54. Although HA shows the same, if not improved, benefits with respect to on‐eye retention and epithelial health compared to CMC and HPMC in the treatment of dry eye disease, it is infrequently used in medicated drops for other eye conditions.…”
Section: Topical Ocular Drug Delivery: Eye Dropsmentioning
confidence: 99%
“…Due to its unique properties, including full biodegradability, biocompatibility, nontoxicity, high water absorption capacity, and nonimmunogenicity [3,4], this biopolymer is widely used for many medical applications. For example, HA is commonly used as an adjuvant for cataract surgery in ophthalmology [5], as a viscosupplement for the treatment of osteoarthritis in rheumatology [6] and for filling wrinkles and/or restoring facial volume in aesthetic medicine [1,7,8].…”
Section: Introductionmentioning
confidence: 99%